The Role of Service Quality, Product Quality, and Price in Creating a Competitive Advantage Coffee Shop in Cirebon City - Ikrimatul Fathiyah; Audita Nuvriasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to examine how price, product quality, and service quality affect a coffee shop's ability to compete in Cirebon City. Using questionnaires and the non-probability sampling approach, 40 respondents made up the study's sample. According to the Instrument Test findings, the study's data turned out to be accurate and genuine. The data in this study were shown to be normally distributed using the Classical Assumption Test, which also yielded a regression model devoid of heterokedasticity and multicollinearity. The study's findings demonstrate that: (1) Cirebon City's coffee shops' competitive advantage is not significantly impacted by service quality. (2) The Cirebon City Coffee Shop's Competitive Advantage is positively and significantly impacted by the quality of Prodik. (3) Cirebon City's Coffee Shop is not greatly impacted by price.